Rapid chemical synthesis method and application of green light emitting carbon dots

By using fructose and oxalic acid as raw materials, condensation and polymerization reactions under the action of calcium oxide, the green light-emitting carbon dots are rapidly synthesized, and the problems of high toxicity of raw materials, serious environmental pollution and long reaction time in the existing technology are solved, and the problem of high toxicity of raw materials is achieved. Efficient and environmentally friendly fluorescent carbon dot synthesis.

CN119432372AInactive Publication Date: 2025-02-14AUCKLAND MEDICAL TECH (SICHUAN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411567270.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the raw materials for synthesizing fluorescent carbon dots are highly toxic, have serious environmental pollution, and have a long reaction time, making it difficult to meet the application needs of the biomedical field.

Method used

Fructose and oxalic acid are used as non-toxic raw materials, and condensation and polymerization reactions are carried out under the action of calcium oxide through magnetic stirring and high-speed centrifugation to quickly synthesize green light-emitting carbon dots.

Benefits of technology

The rapid synthesis of fluorescent carbon dots is achieved, avoiding the use of toxic raw materials, reducing environmental pollution, shortening reaction time, and improving the purity and biocompatibility of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432372A_ABST
    Figure CN119432372A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid chemical synthesis method and application of green light emitting carbon dots, and the method comprises the following steps: adding fructose and oxalic acid into deionized water at normal temperature and pressure, dissolving, magnetically stirring for 0.5-2 hours, then adding calcium oxide, and magnetically stirring for 4-12 hours to obtain a reaction solution; then, the reaction liquid is subjected to high-speed centrifugal treatment, the centrifugal rate is 8000-12000 rpm, the centrifugal time is 5-15 min, precipitates obtained after centrifugation are removed, and a fluorescent carbon dot solution obtained after reaction is obtained; and carrying out freeze drying treatment on the fluorescent carbon dot solution to obtain solid carbon dot powder. The size distribution of the synthesized carbon dot nanoparticles is uniform, the emission wavelength is a green light wave band, the water dispersibility and stability are good, the preparation process is at normal temperature and normal pressure, the energy consumption is low, the method is green and environment-friendly, the reaction rate is improved by using calcium oxide, and the blank that the synthesis time is long and the raw material toxicity is relatively high in the current chemical method is filled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and specifically relates to a rapid chemical synthesis method and application of green light emitting carbon dots. Background Art

[0002] Among the many luminescent materials, quantum dots are a luminescent material with excellent performance and have broad application prospects in optoelectronic devices, energy, biology, medicine and other fields. Although semiconductor quantum dots have the advantages of high luminescence efficiency and adjustable spectral wavelength, their application in the biomedical field is limited by the high toxicity of their raw materials and complex processes. Carbon quantum dots (Cd) as an emerging zero-dimensional carbon-based nanomaterial not only have good optoelectronic properties, but also have a wide range of raw material sources, simple preparation process, and good biocompatibility, thus having very broad application prospects in the biomedical field. At present, the preparation methods of fluorescent carbon dots are mainly divided into two categories: "top-down" and "bottom-up", mainly including hydrothermal method, chemical method, electrochemical oxidation method, laser ablation method, microwave method, etc. Among them, the hydrothermal method is a common method for synthesizing fluorescent carbon dots, but its reaction requires high temperature and high pressure, and the reaction conditions are relatively harsh. Although the electrochemical oxidation method and microwave method are simple, the size distribution range of the synthesized carbon dots is large and the size is not easy to control. The equipment required for synthesizing carbon dots by laser ablation is expensive and the yield is low. In addition, chemical method is also a common method for synthesizing carbon dots. This method is a simple and low-energy synthesis method. At present, it is generally under the action of strong acid or strong base, using ketone aldehyde substances such as acetone or acetaldehyde, and then the ketone aldehyde substances such as acetone or acetaldehyde react and then stand for a period of time to generate fluorescent carbon dots. Although the chemical method currently used can synthesize fluorescent carbon dots, it is simple to operate and has low cost, but the ketone aldehyde substances such as acetone or acetaldehyde used are toxic, which will cause harm to human health, and belong to easy-to-prepare drugs, and will also cause certain pollution to the environment. In addition, the reaction time of preparing fluorescent carbon dots by chemical method is relatively long, generally taking several days, and how to shorten its reaction time is also another problem it faces.

[0003] Therefore, it is particularly necessary to explore a rapid chemical synthesis method for preparing fluorescent carbon dots using green and non-toxic raw materials. Summary of the invention

[0004] In order to overcome the defects of the prior art, the present invention provides a rapid chemical synthesis method and application of green light emitting carbon dots, which can solve the technical problems that the raw materials used in the current chemical synthesis of carbon dots are highly toxic, cause great environmental pollution and have a long reaction cycle.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for rapid chemical synthesis of green light emitting carbon dots, comprising the following steps:

[0007] S1. Add fructose and oxalic acid into deionized water and dissolve them, stir them magnetically for 0.5-2h, then add calcium oxide and stir them magnetically for 4-12h to obtain a reaction solution; S2. Centrifuge the reaction solution at high speed to remove the precipitate to obtain a fluorescent carbon dot solution; S3. Freeze-dry the fluorescent carbon dot solution to obtain a solid carbon dot powder, thus completing the synthesis.

[0008] The principle of the present invention is as follows: In the preparation method, the aldehyde group of fructose and the carboxyl group of oxalic acid are condensed to be converted into unsaturated aldehydes, and then these unsaturated aldehydes undergo polymerization to generate a large number of oligomers. Under the action of calcium oxide, side reactions such as dehydration and dehydrogenation occur rapidly to form extended carbon chains, which are further curled and wound to form carbon dots. The main reaction equation involved in the present invention is as follows: CH2OH(CHOH)3COCH2OH+CH3COOH+CaO→CH2(CHOH)2CHCOCH2·CH3COO+Ca(OH)2+H2O

[0009] The main beneficial effects of the present invention are as follows: compared with other chemical methods that use toxic and polluting ketones or aldehydes such as acetone or formaldehyde as raw materials, the present invention uses non-toxic fructose and oxalic acid and rapidly undergoes a condensation reaction under the action of calcium oxide, which greatly improves the reaction time of the chemical method and avoids the use of toxic reagents.

[0010] In one embodiment, in S1, the mass-to-volume ratio of the fructose to the deionized water is 0.02-0.1 g / mL.

[0011] The main beneficial effects of the present invention are as follows: the use of fructose and deionized water in the mass-volume ratio can fully dissolve the fructose in the deionized water, thereby allowing the fructose to fully participate in subsequent reactions, thereby avoiding fructose precipitation and side reactions.

[0012] In one embodiment, in S1, the mass ratio of the oxalic acid to the fructose is (1-5):1.

[0013] The main beneficial effects of the present invention are as follows: using oxalic acid and fructose in this mass ratio can cause fructose and oxalic acid to undergo a condensation reaction to generate unsaturated aldehydes, while using oxalic acid and fructose in other mass ratios may generate other by-products such as esters, thereby reducing the yield of the target product.

[0014] In one embodiment, in S1, the mass ratio of the oxalic acid to the fructose is 2:1.

[0015] The main beneficial effects of the present invention are as follows: this ratio is the preferred ratio in the above range, and the carbon dots prepared by this ratio have the strongest luminescence effect and the best marking effect.

[0016] In one embodiment, in S1, the mass ratio of the calcium oxide to the fructose is (1-5):1.

[0017] The main beneficial effects of the present invention are as follows: the use of calcium oxide and fructose in this mass ratio can fully dehydrate fructose and oxalic acid to undergo a condensation reaction to generate unsaturated aldehydes. When calcium oxide in other mass ratio ranges is used, fructose and oxalic acid may not be fully dehydrated, resulting in incomplete reaction and reduced yield of the target product.

[0018] In one embodiment, in S1, the mass ratio of the calcium oxide to the fructose is 5:1.

[0019] The main beneficial effects of the present invention are as follows: this ratio is the preferred ratio in the above range, and the carbon dots prepared by this ratio have the strongest luminescence effect and the best marking effect.

[0020] In one embodiment, S1 is performed at normal temperature and pressure.

[0021] The main beneficial effects of the present invention are as follows: the entire S1 only needs to be performed at room temperature and pressure, without the need for additional heating and pressurization, which increases the convenience of the reaction and reduces the difficulty of operation for operators.

[0022] In one embodiment, in S2, the rotation speed of the high-speed centrifugation is 8000-12000 rpm, and the time of the high-speed centrifugation is 5-15 min.

[0023] The main beneficial effects of the present invention are as follows: the rotation speed range and centrifugation time can fully precipitate impurities and improve the purity of the target product.

[0024] In a second aspect, the present invention provides an application of the green light emitting carbon dots mentioned above in cell labeling and cell imaging.

[0025] The beneficial effects of the present invention are:

[0026] The invention uses deionized water as a solvent, fructose as a polyhydroxy aldehyde, oxalic acid as a polyhydroxy ketone, and utilizes the dehydration and polymerization reaction between the aldehyde group and the ketone group to synthesize the fluorescent carbon dots. The chemical reaction between fructose and oxalic acid is promoted by adding calcium oxide to increase the synthesis time of the fluorescent carbon dots. The carbon dots synthesized by the method emit green fluorescence, have good water dispersibility and stability, and the preparation process is at room temperature and pressure, the reaction time is short, the raw materials are fructose and oxalic acid, and the method is green and environmentally friendly, which fills the shortcomings of the current chemical method for synthesizing fluorescent carbon dots, that the raw materials are toxic and the reaction time is long. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein:

[0028] Figure 1 is a transmission electron microscopy image of the synthesized carbon dots when the amount of fructose used in Example 2 is 6 g;

[0029] Figure 2 is the infrared spectrum of the carbon dots synthesized when the amount of fructose used in Example 2 is 6 g;

[0030] Figure 3 is the UV-visible absorption spectrum of the synthesized carbon dots when the amount of fructose used in Example 2 is 6 g;

[0031] Figure 4 is the emission spectra of the synthesized carbon dots when the fructose dosage in Examples 1, 2, and 3 is 2, 6, and 10 g, respectively;

[0032] Figure 5 is the excitation spectrum of the synthesized carbon dots when the amount of fructose used in Example 2 is 6 g;

[0033] Figure 6 is a transmission electron micrograph of the carbon dots synthesized when the amount of oxalic acid used in Example 5 is 12 g;

[0034] Figure 7 is the emission spectra of the synthesized carbon dots when the amounts of oxalic acid used in Examples 4, 5, and 6 are 4, 12, and 20 g, respectively;

[0035] Figure 8 is the excitation spectrum of the synthesized carbon dots when the amount of oxalic acid used in Example 5 is 12 g;

[0036] Fig. 9 is a transmission electron micrograph of carbon dots synthesized when the amount of calcium oxide used in Example 8 is 30 g;

[0037] Fig.10 is the emission spectra of the synthesized carbon dots when the amounts of calcium oxide used in Examples 7, 8 and 9 are 10, 30 and 50 g, respectively;

[0038] Fig.11 This is the excitation spectrum of the synthesized carbon dots when the amount of calcium oxide used in Example 8 is 30g. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings.

[0040] Embodiment 1:

[0041] Step 1: At room temperature and pressure, 2 g of fructose and 10 g of oxalic acid were added to 100 mL of deionized water for dissolution, and magnetically stirred for 0.5 h. Then, 10 g of calcium oxide was added and magnetically stirred for 4 h to obtain a solution after chemical reaction;

[0042] Step 2: subjecting the chemical reaction solution obtained in step 1 to high-speed centrifugation at a centrifugal rate of 8000 rpm for 15 minutes, removing the precipitate after centrifugation, and obtaining a fluorescent carbon dot solution after the reaction;

[0043] Step 3: freeze-dry the fluorescent carbon dot solution obtained in step 2 to obtain solid carbon dot powder.

[0044] Embodiment 2:

[0045] The other steps are the same as those in Example 1, except that the mass of fructose in step 1 is changed from 2 g to 6 g.

[0046] Embodiment 3:

[0047] The other steps are the same as those in Example 1, except that the mass of fructose in step 1 is changed from 2 g to 10 g.

[0048] Test results: Different carbon dot nanoparticles were prepared by changing the amount of fructose, and transmission electron microscopy, infrared spectroscopy, UV-visible absorption spectroscopy, excitation and emission spectroscopy were performed on the different carbon dot nanoparticles. Figure 1 is a transmission electron micrograph of the carbon dots synthesized when the amount of fructose used in Example 2 is 6 g. Figure 1 It can be seen that the particle size of carbon dots is relatively uniform, about 2nm. Figure 2 This is the infrared spectrum of the carbon dots synthesized when the amount of fructose used in Example 2 is 6 g. Figure 2 It can be seen that the carbon dots contain chemical bonds such as OH, CH, C=C, C=O, and CO. Figure 3 This is the UV-visible absorption spectrum of the synthesized carbon dots when the amount of fructose used is 6 g in Example 2. The results show that the carbon dot nanoparticles have an obvious absorption peak at 265 nm. Figure 4 The emission spectra of the synthesized carbon dots in Examples 1, 2, and 3 when the fructose dosage is 2, 6, and 10 g, respectively. Figure 4 It can be seen that the emission wavelength of the carbon dots synthesized with different fructose dosages is in the green light band, and the emission peak is located near 520nm. With the increase of fructose dosage, the emission peak position of the carbon dots does not change significantly, and the emission intensity first increases and then decreases. Figure 5 This is the excitation spectrum of the synthesized carbon dots when the amount of fructose used in Example 2 is 6 g. Figure 5 It can be seen that the excitation wavelength of the synthesized carbon dots is in the ultraviolet-blue light band, with an obvious excitation peak around 420nm.

[0049] Embodiment 4:

[0050] Step 1: At room temperature and pressure, 4 g of fructose and 4 g of oxalic acid were added to 100 mL of deionized water for dissolution, and magnetically stirred for 1 h. Then, 12 g of calcium oxide was added and magnetically stirred for 8 h to obtain a solution after chemical reaction;

[0051] Step 2: subjecting the chemical reaction solution obtained in the previous step to high-speed centrifugation at a centrifugal rate of 10,000 rpm for 10 minutes, removing the precipitate after centrifugation, and obtaining a fluorescent carbon dot solution after the reaction;

[0052] Step 3: freeze-dry the fluorescent carbon dot solution obtained in the previous step to obtain solid carbon dot powder.

[0053] Embodiment 5,

[0054] The other steps are the same as those in Example 4, except that the mass of oxalic acid in step 1 is changed from 4 g to 12 g.

[0055] Embodiment 6,

[0056] The other steps are the same as those in Example 4, except that the mass of oxalic acid in step 1 is changed from 4 g to 20 g.

[0057] Test results: Different carbon dot nanoparticles were prepared by changing the mass of oxalic acid, and the carbon dots were measured by transmission electron microscopy, excitation spectrum and emission spectrum. Figure 6 This is a transmission electron microscope image of the carbon dots synthesized when the amount of oxalic acid used is 12 g in Example 5. Through the transmission electron microscope, it can be observed that the carbon dot particles are relatively uniform, and the particle size is about 2 nm. Figure 7 The emission spectra of the synthesized carbon dots in Examples 4, 5, and 6 when the amounts of oxalic acid used are 4, 12, and 20 g, respectively. Figure 7 It can be seen that the emission spectrum of carbon dots is in the green light band. With the increase of oxalic acid dosage, the emission peak position of carbon dots remains basically unchanged at around 520nm, and the emission peak intensity first increases and then decreases. Figure 8 This is the excitation spectrum of the synthesized carbon dots when the amount of oxalic acid used in Example 5 is 12 g. Figure 8 It can be seen that the excitation spectrum of carbon dots is located in the ultraviolet-blue light band, and the excitation peak is located at around 420nm.

[0058] Embodiment 7:

[0059] Step 1: At room temperature and pressure, 10 g of fructose and 20 g of oxalic acid were added to 100 mL of deionized water for dissolution, and magnetically stirred for 2 h. Then, 10 g of calcium oxide was added and magnetically stirred for 12 h to obtain a chemically reacted solution.

[0060] Step 2: subjecting the chemical reaction solution obtained in the previous step to high-speed centrifugation at a centrifugal rate of 12,000 rpm for 5 minutes, removing the precipitate after centrifugation, and obtaining a fluorescent carbon dot solution after the reaction;

[0061] Step 3: freeze-dry the fluorescent carbon dot solution obtained in the previous step to obtain solid carbon dot powder.

[0062] Embodiment 8:

[0063] The other steps are the same as those in Example 8, except that the mass of calcium oxide in step 1 is changed from 10 g to 30 g.

[0064] Embodiment 9:

[0065] The other steps are the same as those in Example 8, except that the mass of calcium oxide in step 1 is changed from 10 g to 50 g.

[0066] Test results: Different carbon dot nanoparticles were prepared by changing the amount of calcium oxide, and the carbon dots were measured by transmission electron microscopy, excitation spectrum and emission spectrum. Fig. 9 This is a transmission electron microscope image of carbon dots synthesized when the amount of calcium oxide used is 30 g in Example 8. Through the transmission electron microscope, it can be observed that the particles of the carbon dots are relatively uniform, and the particle size is about 2 nm. Fig.10 The emission spectra of the synthesized carbon dots in Examples 7, 8 and 9 when the amount of calcium oxide used was 10, 30 and 50 g respectively. Fig.10 It can be seen that the emission spectrum of carbon dots is located in the green light band. With the increase of calcium oxide dosage, the emission peak position of carbon dots remains basically unchanged at around 520nm, and the emission peak intensity first increases and then decreases. Fig.11 This is the excitation spectrum of the synthesized carbon dots when the amount of calcium oxide used in Example 8 is 30g. Fig.11 It can be seen that the excitation spectrum of carbon dots is located in the ultraviolet-blue light band, and the excitation peak is located at around 420nm.

[0067] According to the above results, it can be seen that the method proposed by the present invention avoids the use of toxic raw materials such as acetone and formaldehyde, and can synthesize fluorescent carbon dots at room temperature without complicated processing technology. The emission spectrum of the carbon dot nanoparticles is in the green light band, and the excitation wavelength is in the ultraviolet band. The invention fills the gap in the technology of preparing fluorescent carbon dots using green raw materials and rapid chemical methods. In addition, the reaction time of fluorescent carbon dots can be adjusted by changing the mass of calcium oxide, and the reaction conditions are mild, the process is simple, and it is easy to mass produce; and when the amount of fructose, oxalic acid and calcium oxide is adjusted within the interval, it will not have a significant impact on the results. When the amount of fructose, oxalic acid and calcium oxide is adjusted, the emission peak intensity at around 520nm increases first and then decreases. It can be seen that when the amount of oxalic acid is 12g, the amount of fructose is 6g, and the amount of calcium oxide is 30g, the emission peak intensity is the highest when added in this proportion.

[0068] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "bottom", "top", "front", "back", "inside", "outside", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0069] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.

Claims

1. A rapid chemical synthesis method of green light emitting carbon dots, characterized in that: The steps include: S1. Add fructose and oxalic acid into deionized water to dissolve, stir magnetically for 0.5-2h, then add calcium oxide and stir magnetically for 4-12h to obtain a reaction solution; S2, centrifuging the reaction solution at high speed to remove the precipitate to obtain a fluorescent carbon dot solution; S3, freeze-drying the fluorescent carbon dot solution to obtain solid carbon dot powder, thus completing the synthesis.

2. The rapid chemical synthesis method of green light emitting carbon dots according to claim 1, characterized in that: In S1, the mass-volume ratio of the fructose to the deionized water is 0.02-0.1 g / mL.

3. The rapid chemical synthesis method of green light emitting carbon dots according to claim 2, characterized in that: In S1, the mass ratio of the oxalic acid to the fructose is (1-5):

1.

4. The rapid chemical synthesis method of green light emitting carbon dots according to claim 2, characterized in that: In S1, the mass ratio of the oxalic acid to the fructose is 2:

1.

5. The rapid chemical synthesis method of green light emitting carbon dots according to claim 2, characterized in that: In S1, the mass ratio of the calcium oxide to the fructose is (1-5):

1.

6. The rapid chemical synthesis method of green light emitting carbon dots according to claim 5, characterized in that: In S1, the mass ratio of the calcium oxide to the fructose is 5:

1.

7. The rapid chemical synthesis method of green light emitting carbon dots according to claim 1, characterized in that: The S1 is performed at normal temperature and pressure.

8. The rapid chemical synthesis method of green light emitting carbon dots according to claim 1, characterized in that: In S2, the rotation speed of the high-speed centrifugation is 8000-12000 rpm, and the time of the high-speed centrifugation is 5-15 min.

9. Use of the green light emitting carbon dots according to any one of claims 1 to 8 in cell labeling and cell imaging.

Citation Information

Patent Citations

  • Application of fluorescence inner filter effect based carbon nano point

    CN103592268A

  • Rapid preparation method of carbon quantum dots

    CN107934936A

  • Pure carbon nanodots, preparation method thereof and LED light source

    CN108587614A